Russian Preposition v kachestve and its French Equivalent à titre de as a Means of Forming the Constructions of Identity in Russian and French Languages - Z. V. Sheremetyeva (Научный диалог, 2017)
The results of the analysis of contextual uses of the Russian derived preposition v kachestve and one of its French equivalents - prepositional expression à titre de - are presented. The relevance of the study stems from the importance of the category of “identity” for the human understanding of the world and from the need of a detailed study of the phenomena representing this concept. The novelty of the study lies in the choice of units for analysis and the approach to their description. The material was journalistic texts in two languages chosen from text databases (text corpus and newspapers archives). The work briefly reviews the linguistic literature devoted to the phenomenon of identity, special attention is paid to indicators and means of expression of identity in language. The question about the existence of special types of syntactic constructions with the meaning of identity, introduced by some prepositional units, in the Russian and French languages is raised. It is proved that the Russian preposition v kachestve and the French prepositional expression à titre de can establish relations of identity (functional and ontological) between the components within syntax. The author concludes that both examined prepositional units can be considered the indicators of identity along with other morphological and lexical indicators.